The Impact of Principal’s Leadership Style and Academic Supervision on the Teachers’ Professionalism - Astria, Rani; Arafat, Yasir; Eddy, Syaiful (Journal of Social Work and Science Education, 2025)
This study determines the influence of the principal’s leadership style and academic supervision on teachers’ professionalism partially and simultaneously at SD Negeri Kecamatan Ilir Barat I. The approach used is quantitative with a descriptive method. The population consists of 390 civil servant teachers and principals, with 129 teachers selected as the sample using proportional stratified random sampling. Data were collected through questionnaires, observations, and documentation. Data analysis includes tests for validity, reliability, normality, multicollinearity, and heteroscedasticity, followed by multiple linear regression, t-test, F-test, and coefficient of determination (R²). The results showed that 1) the principal’s leadership style has a positive and significant influence on teacher professionalism, 2) academic supervision has a positive and significant influence on teacher professionalism, and 3) both variables simultaneously have a significant influence on teacher professionalism. These findings emphasize the importance of effective leadership and high-quality academic supervision in enhancing teacher professionalism and the quality of basic education.